1015 Design and evaluation of novel irish drowning data taxonomies for a fatalities database. (1st September 2016) - Kervick, Aoife; Summerville, Sarah; Dix, Dani; Walters, Thomas; Sweeney, Roger; Sarma, Kiran
Abstract : Background: In the Republic of Ireland (ROI) 135 people drown annually, the majority of which are preventable deaths. Currently, substantial opportunities exist to develop upon the existing methods of managing fatality data in the ROI. The current study thus aimed to develop and evaluate a set of novel drowning data taxonomies, to better record drowning deaths in Irish waters. Improvements to this fatalities taxonomy will enhance accurate incident recording, and benefit subsequent intervention design. Methods: Development of the ROI taxonomies was fourfold. First, member groups of the International Life Saving Federation (ILSF) were contacted for access to any drowning related data taxonomies available to them. A comparison study of the different taxonomies accessed through the email campaign was then conducted. Analyses involved contrasting and comparing items from the selected taxonomies and identifying valuable details for inclusion in the ROI set. Materials relevant to an Irish context were then adapted, and the taxonomies created. Last, a host of ROI-based water safety experts reviewed the proposed taxonomies during an interactive stakeholder workshop. This was conducted using the Interactive Management (IM) methodology, and yielded valuable recommendations, which were then incorporated to produce the definitive set of drowning data taxonomies. Results: A novel set of drowning data taxonomies were designed and completed. These were evaluated favourably during the stakeholder workshop, with any expert feedback acknowledged and incorporated. Conclusions: The quality of drowning fatality data records in the ROI can be improved by the current project activities. These taxonomies will be used to populate a drowning fatalities database, currently being designed in conjunction with this study. These will ultimately provide a high quality evidence base from which to inform intervention design in the ROI, and prevent further drowning fatalities.